Respostas

2014-06-18T08:17:46-03:00
Como Eu posso resolver ?
3x(x-2)-3x(2x+2)=0       fazer a distributiva

3x² -6x - 6x² - 6x = 0
3x² - 6x² -6x-6x = 0
-3x² -12x = 0      (podemos fazer em evidencia ou pela BASKARA)
 
1º) PELA EVIDÊNCIA
-3x² - 12x = 0
3x(-x -4) = 0

3x = 0
x' = 0

(-x-4) = 0
-x - 4 = 0
-x = + 4
x" = - 4


2º) pela BASKARA

-3x² - 12x = 0
a = -3
b = -12
c = 0
Δ = b² - 4ac
Δ = (-12)² - 4(-3)(0)
Δ = 144 -     0
Δ = 144 ----------------------------------√144 = 12

se

Δ > 0

então

x = - b - + 
√Δ/2a

x' = -(-12) -
√144/2(-3)
x' = + 12 - 12/-6
x' = 0/6
x' = 0

x" = -(-12) + 
√144/2(-3)
x" = + 12 + 12/-6
x" = 24/-6
x" = - 24/6
x" = - 4
 
V = { -4, 0}